The Effectiveness of the Example Non Example Learning Model assisted by Nearpod Media to Improve the Analysis and Communication Skills of Reproductive System Material - Anisatul Latifah; Eling Purwantoyo (Universitas Negeri Semarang, 2025)
The purpose of the study was to analyze the effectiveness of the Example Non Example learning model assisted by Nearpod media to improve students' analysis and communication skills on Reproductive System material. This type of research is a quasi experiment with a non-equivalent control group design with pretest and posttest. The research sample consisted of students of XI MIPA 6 class as the experimental class and XI MIPA 7 as the control class. Data were collected through tests, observations, and questionnaires. The data were analyzed statistically quantitative and test (N-gain). The results showed: 1) the example non example learning model assisted by nearpod media can improve students' analytical skills, this is evidenced by the increase from the pretest to the posttest results of the experimental class higher than the control class, namely in the experimental class getting 65% results while in the control class getting 50% results; 2) the example non example learning model assisted by nearpod media can improve students' communication skills, this is evidenced by the increase in communication observation results of the experimental class at the initial meeting 49% increased at the final meeting to 89%